2017
DOI: 10.1093/heapro/dax066
|View full text |Cite
|
Sign up to set email alerts
|

Do Israeli health promoting schools contribute to students’ healthy eating and physical activity habits?

Abstract: The Israeli Health Promoting School Network (HPSN) is actively committed to enhancing a healthy lifestyle for the entire school population. This study aimed to explore the contribution of school participation in the HPSN and students' individual characteristics to healthy eating and physical activity habits among Israeli school children aged 10-12 years. A cross-sectional survey was conducted among 4166 students in grades 4-6 from 28 schools. The schools were selected from a sample of HPSN affiliated and non-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Schools that agree to join in the network are committed to achieving educational objectives, in addition to promoting student health and improving the quality of life and well-being of the school community. The Israeli HPS is based on the international network approach and belongs to it [31].…”
Section: Independent Variablesmentioning
confidence: 99%
“…Schools that agree to join in the network are committed to achieving educational objectives, in addition to promoting student health and improving the quality of life and well-being of the school community. The Israeli HPS is based on the international network approach and belongs to it [31].…”
Section: Independent Variablesmentioning
confidence: 99%
“…We also found that only 1 (2%) made secondary use of existing surveys, and only 4 (8%) consisted of assessments of existing or potential national policy interventions or programs. The national policy interventions or programs assessed were: national reforms in mental health and social care services [ 15 ], financial incentives to attract medical residents to the periphery [ 16 ], and the health promoting schools network [ 17 ], and a potential policy of government sharing of financial risks with health plans [ 18 ]. 8 The only article in the collection to employ secondary analysis of an existing data set used data from the Survey of Health, Ageing and Retirement in Europe (SHARE) at two selected time points (2006/2007 and 2015) to investigate changes in the rate of informal care provision, which occurred in Israel and Italy in the last decade [ 19 ].…”
Section: Appendixmentioning
confidence: 99%
“…The national policy interventions or programs assessed were: national reforms in mental health and social care services [ 15 ], financial incentives to attract medical residents to the periphery [ 16 ], and the health promoting schools network [ 17 ], and a potential policy of government sharing of financial risks with health plans [ 18 ]. 8…”
Section: Appendixmentioning
confidence: 99%
“…Recent works addressing diverse areas in Israel’s food system include food security [ 13 ], food welfare, food prices and economic policy [ 4 ], agricultural production [ 17 ], food waste [ 25 ], food and public health [ 9 , 14 ], environmental impacts and sustainability [ 12 , 30 , 33 ], and food systems and society [ 15 ]. However, there are insufficient academic studies addressing Israel’s food system in an integrated and multidisciplinary manner.…”
Section: Introduction/backgroundmentioning
confidence: 99%